Innovations in insuring the poor: Providing weather index and indemnity insurance in Ethiopia - Meherette, Eyob (International Food Policy Research Institute, 2009)
Agriculture in Ethiopia is almost entirely rainfed and highly prone to droughts and floods. Given that 85 percent of the population depends on smallholder agriculture, these weather shocks severely affect many Ethiopians. The high covariance of climatic risks, coupled with the lack of property to be attached as collateral, makes it difficult for cooperatives, microfinance organizations, or banks to provide financial services to smallholder farmers unless they have some insurance/reinsurance against this weather risk. These conditions in turn keep farming at a subsistence level, with low use of improved technology, low productivity, and low risk. Nyala Insurance S.C. is one of the leading private insurance companies in Ethiopia and provides a range of products, including both life insurance and general insurance. To help farmers protect themselves against droughts that significantly reduce crop yields, Nyala recently introduced crop insurance products.